Asuhan Kebidanan Continuity of Care (COC) Ny. M G2P1A0 hamil 40 minggu di Tempat Praktek Mandiri Bidan: Midwifery Care Continuity of Care (CoC) Mrs. M G2P1A040 Weeks Pregnant at Independent Midwife Practice - Fitria, Fitria Endah Purwani; Ernawati; Rizka Kasilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Based on the regulation of the Minister of Health of the Republic of Indonesia 320 of 2020 concerning professional standars for midwives, the authority of midwives is maternal health services, child health services, and women’s reproducyive health services and family planning. The purpose of writing this article is to provide comprehensive care for Mrs”M” 26 years old G2P1A0 at TPMB Fitria Endah Purwani, SST.,M.Keb. research method: the research design used is descriptive and the type of research is case study. Guidelines for observation, interviews and documentation studies in the form of midwifery care (SOAP) format. Result: the di diagnosis obtained from the examination result was G2P1A0 39weeks pregnant in partu during the first active phase, live single fetus with head presentasion. Delivery time Mrs. the active phase “M